Determination of Rare Earth Elements by Inductively Coupled Plasma–Tandem Quadrupole Mass Spectrometry With Nitrous Oxide as the Reaction Gas - Zhu, Yanbei (Frontiers in Chemistry, 2022)
Nitrous oxide (N2O) was investigated as the reaction gas for determination of rare earth elements (REEs) by inductively coupled plasma tandem quadrupole mass spectrometry (ICP-QMS/QMS). The use of N2O as the reaction gas apparently improved the yields of mM16O+ for Eu and Yb in the reaction cell. As a result, the sensitivities for measurement of Eu and Yb were apparently improved in comparison to those obtained with O2 as the reaction gas. High sensitivity measurement of the whole set of REEs was achieved, providing a typical sensitivity of 300,000 CPS mL/ng for REEs measured with an isotope having isotopic abundance close to 100 %. The use of N2O as the reaction gas helped to suppress Ba related spectral interferences with the measurement of Eu, permitting the measurement of Eu in natural sample without mathematic correction of spectral interferences. The detection limits (unit, pg/mL) for 14 REEs (except for Pm) from La to Lu were 0.028, 0.018, 0.006, 0.026, 0.006, 0.010, 0.017, 0.006, 0.016, 0.010, 0.016, 0.004, 0.023, and 0.012, respectively. The validity of the present method was confirmed by determining REEs in river water certified reference materials, i.e. SLRS-3 and SLRS-4.